Efficient EER-LEACH Protocol for Monitoring the Activities of Pregnant Women Using Wearable Body Sensor Network - Subalakshmi, S; Murugaboopathi, G; Senthilkumar, D (International Journal of Engineering and Technology, 2018)
In health care monitoring framework, it is important to always screen the patient's physiological parameters. For instance, pregnant lady parameters, like, blood pressure, uterine contraction heart rate of pregnant ladies and heart rate alongside the fetal development to detect their wellbeing condition. This paper introduces a monitoring framework that has the capacity to screen physiological changes from the pregnant ladies. In the proposed framework, controller node (CN) has connected on patient body to gather every one of the signs from the uterine contraction monitoring wearable body sensors and sends them to the base station. The appended sensors on patient's body frame a wireless body sensor network (WBSN) and they can detect the uterine constriction, heart rate, blood pressure etc. This framework can recognize the unusual conditions, issue an alert to the patient and send to the doctor. Likewise, the proposed framework comprises of a few relay nodes which are in charge of handing-off the information sent by the controller node (CN) and forward them to the base station. The principle effort of this framework is to diminish the vitality utilization to delay the system lifetime, accelerate and stretch out anticipated work is to expand the sensor execution. This framework is likewise created for multi-patient observing for hospital healthcare and contrasted with the current systems in view of coverage, energy utilization and speed.Â Â